Secondary School Students’ Perception towards English Teachers’ Strategies in Teaching Speaking in the East Coast of Peninsular Malaysia - Ariffin, Maizurah Kamarull; Yusoff, Nor Asiah; Mohamad Yusof, Nurdiyana (Selangor Humaniora Review, 2021)
Speaking is often ignored by some teachers, resulting in students’ lack of opportunities to practice English during classes and apprehensive in utilizing the language promptly. Teaching speaking is the way to provide the students with the knowledge on how to communicate efficiently. This research aims to identify the effective speaking strategies activities based on students’ perspectives and identify the strategies implemented by English teachers in teaching speaking. This research uses a quantitative method involving two surveys for teachers and students. The questionnaire was distributed using an online platform called Google Form among 135 students from Pahang, Terengganu, and Kelantan and 38 English teachers as the subjects of the study. The data is analyzed using descriptive analysis. It is revealed that the students preferred to use Crazy Stories and Role Play or Simulation activities as they were more effective. The teaching strategies used by English teachers contrasted as they used Discussion Group for students’ oral activities practices. The findings of the study may be used as a reference for future researchers to build the students’ confidence in speaking based on their preferred speaking activities.